2020
DOI: 10.1016/j.cvdhj.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive artificial intelligence–enabled electrocardiogram interpretation program

Abstract: BACKGROUND Automated computerized electrocardiogram (ECG) interpretation algorithms are designed to enhance physician ECG interpretation, minimize medical error, and expedite clinical workflow. However, the performance of current computer algorithms is notoriously inconsistent. We aimed to develop and validate an artificial intelligence-enabled ECG (AI-ECG) algorithm capable of comprehensive 12-lead ECG interpretation with accuracy comparable to practicing cardiologists. METHODSWe developed an AI-ECG algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The study was the first report to show a better performance of machine learning to predict echocardiographic LAE compared to the traditional ECG criterion of P wave duration in young male adults who had a healthy status and without multiple comorbidities. Prior studies ( 29 31 ) have revealed that machine learning for ECG features could detect most of the LAE cases from hospitalized patients, probably due to those patients with LAE who were likely to have other cardiac comorbidities, such as heart failure, that were easily reflected by ECG features; thus, the results might not be appropriate for healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was the first report to show a better performance of machine learning to predict echocardiographic LAE compared to the traditional ECG criterion of P wave duration in young male adults who had a healthy status and without multiple comorbidities. Prior studies ( 29 31 ) have revealed that machine learning for ECG features could detect most of the LAE cases from hospitalized patients, probably due to those patients with LAE who were likely to have other cardiac comorbidities, such as heart failure, that were easily reflected by ECG features; thus, the results might not be appropriate for healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The study was the first report to show a better performance of machine learning to predict echocardiographic LAE compared to the traditional ECG criterion of P wave duration in young male adults who had a healthy status and without multiple comorbidities. Prior studies (29)(30)(31) have revealed that machine learning for ECG features could detect most of the LAE cases from hospitalized patients, probably due to those patients with LAE who were likely to have other cardiac comorbidities, such as heart failure, that were easily reflected by ECG features; thus, the results might not be appropriate for healthy individuals. Some studies have shown that, in young adults, particularly physically fit people, an enlarged cardiac chamber is likely, and the typical ECG features for LAE might not be the same as those in middle-aged individuals and elderly individuals who had several cardiovascular comorbidities, i.e., hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further improvement of the diagnostic accuracy has the potential to transform wearables, such as smartwatches, from screening and pre-diagnostic tools to diagnostic modalities. The integration of artificial intelligence algorithms in basic medical tools, such as the 12-lead ECG, has demonstrated promising results, regarding the early and accurate detection of structural heart disorders, thus extending beyond the field of arrhythmia diagnosis ( 121 , 122 ). The combination of this technological advancement with wearable devices could improve the reliability of their measurements and provide prognostic features for the detection of subclinical cardiac conditions ( 123 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Publications on the use of AI for 12 lead ECG interpretation are already appearing [60,61]. A recent study by Kashou et al states that their AI-based approach 'outperforms an existing standard automated computer program' and also 'better approximates expert over-read for comprehensive 12 lead ECG interpretation' [62].…”
Section: Machine Learningmentioning
confidence: 99%